Assessment of the Effect of Agricultural Machinery Trafficking on Soil Compaction: A Case Study of Tamela Farm Site, Oromia Seed Enterprise - Abera, Feyisa (ASTU, 2024)
Technology has increased agricultural productivity, but it also increases the weight of equipment and its use, potentially due to soil compaction. Soil compaction, a process that reduces air-filled soil pores, negatively impacts crop yield and reduces root growth and plant development, reducing agricultural output. According to the OSE annual report, average wheat and barley yields at the Tamela site have decreased by 3.3 quintals per hectare and 1.825 quintals per hectare per year, respectively, from 2019 to 2022. The study aims to evaluate the effect of agricultural machinery trafficking on soil compaction. The research experiment was done at Tamela Farm Site, Oromia Seed Enterprise. A four-wheeled 92.3 kN tractor was used in the experiments. The correlations between load, depth, and the number of passes for both bulk density and penetration resistance were described using multiple linear regressions. Three replications were performed for each of the three normal load levels used in the experiment, which were 30 kN, 33 kN, and 36 kN. The information gathered at depths of 0–15 cm, 15–30 cm, 30-45 cm, and 45–60 cm using the sand replacement technique and the dynamic cone penetrometer, respectively, the field bulk density and penetration resistance were assessed under various loading conditions and1,5,10,and 15 numbers of passes. Using an analytical tool from a computer package (MS-Excel and Minitab), the data was examined. With a 95% confidence level and a p value of 0.05. The soil type was classified as sandy clay loam texture. According to the findings, the second soil layer's bulk density at 36 kN and 15 passes was 1494 kg/m3. The subsurface layer below 45–60 cm at 30 kN and one pass had the lowest bulk density of 1150 kg/m3. The maximum penetration resistance was discovered to be 153 J/cm at 36 kN and a depth below 45–60 cm. On the topsoil layer, the lowest penetration resistance measured was 9.52 J/cm at 30 kN. During the test period, the moisture content average was 24.084%. According to the results, the BD and SPR rose as the payload and number of passes increased. The coefficients of determination (R2) for bulk density and penetration resistance were found to be of 0.8724and 0.8674, respectively. Tamela farm sites are advised to minimize the number of passes and wheel loads; plant operators should be trained to reduce the number of runs on the same tire track. Deep tillage operations, often known as sub-soiling, should only be used on compacted soils. The use of appropriate field equipment, the absorption of organic matter into the soil, and the practice of crop rotation could all help to prevent soil compaction.

Technology Has Increased Agricultural Productivity, But It Also Increases The Weight Of Equipment And Its Use, Potentially Due To Soil Compaction. Soil Compaction, A Process That Reduces Air-Filled Soil Pores, Negatively Impacts Crop Yield And Reduces Root Growth And Plant Development, Reducing Agricultural Output. According To The Ose Annual Report, Average Wheat And Barley Yields At The Tamela Site Have Decreased By 3.3 Quintals Per Hectare And 1.825 Quintals Per Hectare Per Year, Respectively, From 2019 To 2022. The Study Aims To Evaluate The Effect Of Agricultural Machinery Trafficking On Soil Compaction. The Research Experiment Was Done At Tamela Farm Site, Oromia Seed Enterprise. A Four-Wheeled 92.3 Kn Tractor Was Used In The Experiments. The Correlations Between Load, Depth, And The Number Of Passes For Both Bulk Density And Penetration Resistance Were Described Using Multiple Linear Regressions. Three Replications Were Performed For Each Of The Three Normal Load Levels Used In The Experiment, Which Were 30 Kn, 33 Kn, And 36 Kn. The Information Gathered At Depths Of 0??15 Cm, 15??30 Cm, 30-45 Cm, And 45??60 Cm Using The Sand Replacement Technique And The Dynamic Cone Penetrometer, Respectively, The Field Bulk Density And Penetration Resistance Were Assessed Under Various Loading Conditions And1,5,10,And 15 Numbers Of Passes. Using An Analytical Tool From A Computer Package (Ms-Excel And Minitab), The Data Was Examined. With A 95% Confidence Level And A P Value Of 0.05. The Soil Type Was Classified As Sandy Clay Loam Texture. According To The Findings, The Second Soil Layer's Bulk Density At 36 Kn And 15 Passes Was 1494 Kg/M3. The Subsurface Layer Below 45??60 Cm At 30 Kn And One Pass Had The Lowest Bulk Density Of 1150 Kg/M3. The Maximum Penetration Resistance Was Discovered To Be 153 J/Cm At 36 Kn And A Depth Below 45??60 Cm. On The Topsoil Layer, The Lowest Penetration Resistance Measured Was 9.52 J/Cm At 30 Kn. During The Test Period, The Moisture Content Average Was 24.084%. According To The Results, The Bd And Spr Rose As The Payload And Number Of Passes Increased. The Coefficients Of Determination (R2) For Bulk Density And Penetration Resistance Were Found To Be Of 0.8724and 0.8674, Respectively. Tamela Farm Sites Are Advised To Minimize The Number Of Passes And Wheel Loads; Plant Operators Should Be Trained To Reduce The Number Of Runs On The Same Tire Track. Deep Tillage Operations, Often Known As Sub-Soiling, Should Only Be Used On Compacted Soils. The Use Of Appropriate Field Equipment, The Absorption Of Organic Matter Into The Soil, And The Practice Of Crop Rotation Could All Help To Prevent Soil Compaction.
Assessment Of The Effect Of Agricultural Machinery Trafficking On Soil Compaction: A Case Study Of Tamela Farm Site, Oromia Seed Enterprise
Keywords: Bulky Density, Machinery, Penetration Resistance, Soil Compaction, and Traffic; Bulky Density, Machinery, Penetration Resistance, Soil Compaction, And Traffic